Antimicrobial activities of curcumin extracted from selected Zingiberaceae species as potential halal active pharmaceutical ingredient - Abu Bakar, Ainaa Eliah; Othman, Rashidi; Mohtar, Mastura; Mohd Latiff, Nur Hanie; Wan Sulaiman, Wan Syibrah Hanisah; Mohd Hatta, Farah Ayuni; Ramya, Razanah (Universiti Islam Sultan Sharif Ali (UNISSA), 2023)
The ginger family (Zingiberaceae) includes plants with a distinct smell and taste that are commonly used as spices in the kitchen, but also in a variety of industries (pharmaceutical, medical, and cosmetic) due to their demonstrated biological activity. This study describes the antibacterial activity of curcumin extracts from selected species of the Zingiberaceae family namely “temu emas” (Curcuma zeodoria). “temu kunci” (Curcuma manga), “temu pauh” (Curcuma amada), “lempoyang” (Zingiber zerumbit) and “cekur” (Kaempferia galangal). Extracts of these compounds were studied on Staphylococcus aureus (ATCC 25923), Escherichia coli (ATCC 35218), Salmonella typhimurium (ATCC 14028), Candida albicans (ATCC 10231) and Aspergilus brasiliensis (ATCC 16404). Turbidity is taken as an indication of growth, thus the lowest concentration, which remains clear after macroscopic evaluation is taken as the minimum inhibitory concentration (MIC). In conclusion, amongst the studied members of Zingiberaceae, temu emas curcumin natural pigment extracts showed the best antibacterial activities against E. coli ATCC 35218 (2 μg / μL), S. typhimurium ATCC 14028 (2 μg / μL), C. albicans ATCC 10231 (2 μg / μL), A. brasiliensis ATCC 16404 (2 μg / μL) and S. aureus ATCC 25923 (3 μg / μL). The outcome of this research will be contributing towards new natural carotenoid pigment sources as potential active pharmaceutical ingredients which can be beneficial to halal health-promoting products industry.